Melatonin reverts CGRP expression induced by capsaicin - Tanuri, Fabiano da Cunha; Amado, Debora; Lima, Eliangela de; Dangoni Filho, Iron; Peres, Mario Fernando Prieto (Headache Medicine, 2019)
Introduction: CGRP, a neuropeptide synthetized and released in the central nervous system and potent vasodilator, has been implicated in migraine physiopathology. Because of that, there are CGRP targeted therapies that decrease CGRP levels. Melatonin, a pineal gland secretion, has already proved its analgesic effect. We aimed to study CGRP expression in an animal model comparing capsaicin, CGRP and melatonin. Methods: We used in our study male animal rats and separated them into groups based in the kind of received solution (control group, capsaicin only and melatonin plus capsaicin). It was prepared brain stem slices and measured the CGRP levels in the trigemino nucleus caudalis (TNC). Results: Capsaicin group (N = 5) presented low intensity of GCRP expression and animals that received capsaicin plus melatonin (N = 5) showed high intensity of CGRP expression compared to capsaicin group. Conclusion: Melatonin decreases CGRP in an experimental model in rats induced by capsaicin, reducing its inflammatory action in cerebral vessels.